Current assessment of polo-like kinases as anti-tumor drug targets. (July 2014) - Craig, Sandra N; Wyatt, Michael D; McInnes, Campbell
<x xml:space="preserve">Abstract</x> Introduction: Polo-like kinase (PLK)1 is the most studied of the PLK family and is a serine/threonine kinase that plays pivotal roles in many aspects of mitosis and hence its deregulation is prevalent in various malignant tumor types. Areas covered: In this review, the authors discuss the relevancy of PLK1 and other PLK members as oncology targets in light of known roles of these kinases and the observed phenotypic consequence of downregulating their activity, depending on how they are targeted. Furthermore, they also discuss the pathways mutated in cancer that have been shown to enhance sensitivity toward PLK1 inhibitors in the context of tumor types that possess these molecular defects. They also summarize preclinical and clinical investigations that have been undertaken for both ATP and non-ATP competitive inhibitors. Expert opinion: PLKs 2, 3 and 5 are primarily linked with tumor suppressor functions and as PLK1 is the most validated anticancer drug target, selective inhibitors for its activities are most likely to result in effective therapeutics with reduced side effects. In this regard, the polo box domain can be targeted to generate selective inhibitors of PLK1 while preventing inhibition of kinases outside of this family. Recent studies confirming the synthetic lethality of other molecular defects with PLK1 can be exploited to obtain tumor selective apoptosis in p53, KRAS and PTEN mutant cancers.